Back Cover. (17th August 2017) - Aronoff, David M.; Correa, Hernan; Rogers, Lisa M.; Arav‐Boger, Ravit; Alcendor, Donald J.
Abstract : The cover image is based on the Original Article Placental pericytes and cytomegalovirus infectivity: Implications for HCMV placental pathology and congenital disease by David M. Aronoff et al., DOI10.1111/aji.12728 . Supported by: Research Centers in Minority Institutions (RCMI) (U54MD007586‐01) and The Meharry Zika Startup Grant